Spatial Diversity in the Socio-Economic Development in Sub-Saharan Africa as Measured by a Composite Index - Agnieszka Witoń (Entrepreneurial Business and Economics Review)
The main aim of the article is to present the level of the socio-economic development in Sub-Saharan Africa's sub-regions: West Africa, South Africa, East Africa, and Central Africa. The second aim is to identify whether some of the sub-regions have significantly different level of the socio-economic development in comparison to the others.